Evaluation of trust in a virtual team - Mat Seman, Noor Azlinda (2014)
Due to the growth of communication technologies, virtual teams have become more common in software industry. However, virtual teams are still having issues in developing and building trust among their team members across the space, time and culture. This study was conducted to determine the main components of trust that are important in building trust among the members and to identify the impact of computer-mediated communications towards trust development among the team members. The study used a quantitative survey method using a questionnaire instrument. Respondents for real study consist of 40 members of virtual teams in IT department. A trust model was produced as a result of the study and the main constructs of trust that were identified are ability, benevolence, integrity and communication. The finding shows that ability and integrity constructs have strong relation with trust. However, only ability construct is identified as a main contributor towards trust.